Sensory acceptability of sweet potatoes: Influence of the cultivar, cooking method and the city - Sosa, Miriam (2023)
Background: This study aimed to evaluate the sensory acceptability of 4 sweet potato cultivars (Beauregard, Morada-INTA, Colorado-INTA and Arapey), considering two cooking methods: boiled and baked; and two cities, 9 de Julio (9DJ) and San Pedro (SP), of Buenos Aires province. 120 women were recruited in each city. A Home Use Test (HUT) was carried out. Each consumer received at home each sample in a bag containing 3 sweet potatoes and the evaluation form. The sensory acceptability of different characteristics of the samples was evaluated, before and after cooking. To inquire the reasons for consumption of each sample, the methodology Check All That Apply (CATA) were used. ─ Results: Of the 2 factors evaluated (city and cooking method), city had a significant influence when evaluating the samples. Participants of SP gave higher acceptability to Beauregard cultivar than 9DJ in most attributes. Colorado INTA had greater acceptability in some descriptors by the consumers of 9DJ. While Arapey and Morada INTA had greatest acceptability in 9DJ trial. In CATA results 9DJ consumers associated the Beauregard cultivar with negative phrases: It tastes weird and It has little flavor/tasteless and to lesser extent to The internal color is artificial and It breaks when cooking. While SP consumers characterized with negative phrases the Arapey and Morada INTA samples as: It changes color (brown) quickly, Its shape is not regular and When cooked, it has threads or fibers. ─ Conclusion: Consumer preferences provide opportunities for development or improvement of new cultivars. It would be interesting to extend this study to other regions and/or countries.